Management for the Internal Supervision System to Develop Educational Quality of School Administrators in the Phrao 4 Educational Quality Development Network Group Under the Chiang Mai Primary Educational Service Area Office 2. - วันต๊ะ, ปุญญิสา; Bunmaphi , Tassanee; Munkhian, Phuwanat; deethung, Sirinnicha (Journal of MCU Phetchaburi Review, 2026)
This research aimed to study (1) Management for the internal supervision system to Develop Educational Quality of School Administrators in the Phrao 4 Educational Quality Development Network Group Under the Chiang Mai Primary Educational Service Area Office 2. and (2) to study the guidelines for Management for the Internal Supesvision System to Develop Educational Quality of School Administrators in the Phrao 4 Educational Quality Development Network Group Under the Chiang Mai Primary Educational Service Area Office 2. This research was a mixed methods study consisting of quantitative data collection using questionnaires from the population, namely administrators, teachers, and personnel in the Phrao 4 Educational Quality Development Network under the Chiang Mai Primary Educational Service Area Office 2, consisting of 4 schools, totaling 74 people, and qualitative data collection through interviews with 5 experts, consisting of 1 educational supervisor responsible for internal supervision, 2 school principals with the rank of Special Expert, 1 deputy school principal, and 1 teacher with the rank of Special Expert. The research results showed that the overall results were at the highest level. The aspects ranked in descending order of average scores are as follows: Measurement and Evaluation; followed by the Supervision Process; then Networking, Dissemination, and Expansion of Supervision; and finally, Planning and Development. Regarding Planning, the emphasis should be on participation, analyzing needs collaboratively with teachers, establishing PLC (Professional Learning Community) groups, and acting as facilitators and resource providers, with a focus on quantitative outcomes. For the Supervision Process, the emphasis should be on strategic planning linked to the school's vision, with administrators providing specific guidance through a supervision cycle including pre- and post-meeting sessions to foster understanding of teachers' contexts. For Measurement and Evaluation, the success of internal supervision in measurement and evaluation should be assessed through empirical data analysis of improved student achievement and evaluation of teachers' assessment tools. Finally, for Networking, Dissemination, and Expansion of Supervision, the focus should be on developing management practices to recognize and honor teachers with outstanding achievements in measurement and evaluation.